Sevoflurane and Hypercapnia Blunt the Physiological Variability of Spontaneous Breathing: A Comparative Interventional Study - Balogh, Adam L.; Sudy, Roberta; Petak, Ferenc; Habre, Walid; Dos Santos Rocha, Andre (Frontiers in Physiology, 2022)
Background: Although spontaneous breathing is known to exhibit substantial physiological fluctuation that contributes to alveolar recruitment, changes in the variability of the respiratory pattern following inhalation of carbon dioxide (CO2) and volatile anesthetics have not been characterized. Therefore, we aimed at comparing the indices of breathing variability under wakefulness, sleep, hypercapnia and sedative and anesthetic concentrations of sevoflurane. Methods: Spontaneous breathing pattern was recorded on two consecutive days in six rabbits using open whole-body plethysmography under wakefulness and spontaneous sleep and following inhalation of 5% CO2, 2% sevoflurane (0.5 MAC) and 4% (1 MAC) sevoflurane. Tidal volume (VT), respiratory rate (RR), minute ventilation (MV), inspiratory time (TI) and mean inspiratory flow (VT/TI) were calculated from the pressure fluctuations in the plethysmograph. Means and coefficients of variation were calculated for each measured variable. Autoregressive model fitting was applied to estimate the relative contributions of random, correlated, and oscillatory behavior to the total variance. Results: Physiological sleep decreased MV by lowering RR without affecting VT. Hypercapnia increased MV by elevating VT. Sedative and anesthetic concentrations of sevoflurane increased VT but decreased MV due to a decrease in RR. Compared to the awake stage, CO2 had no effect on VT/TI while sevoflurane depressed significantly the mean inspiratory flow. Compared to wakefulness, the variability in VT, RR, MV, TI and VT/TI were not affected by sleep but were all significantly decreased by CO2 and sevoflurane. The variance of TI originating from correlated behavior was significantly decreased by both concentrations of sevoflurane compared to the awake and asleep conditions. Conclusions: The variability of spontaneous breathing during physiological sleep and sevoflurane-induced anesthesia differed fundamentally, with the volatile agent diminishing markedly the fluctuations in respiratory volume, inspiratory airflow and breathing frequency. These findings may suggest the increased risk of lung derecruitment during procedures under sevoflurane in which spontaneous breathing is maintained.